The association between metal exposure in follicular fluid and PCOS risk in reproductive-aged women: Mediating Roles of LH/FSH ratio and androgens - Xin Wang; Xueting Lai; Chenke Pan; Tao Yin; Wei Zhu; Xinyue Zhu; Jian Chen; Chunmei Liang; Dongmei Ji (Ecotoxicology and Environmental Safety)
The associations between trace elements levels and the risk of polycystic ovary syndrome (PCOS), particularly main contributor and their joint effect, are limited and elusive. In this case-control study, we involved 388 women with PCOS and 465 controls. We measured eighteen (aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, copper, zinc, selenium, arsenic, cadmium, barium, mercury, lead, strontium, stannum, thallium) in follicular fluid through inductively coupled plasma–mass spectrometry (ICP-MS). Based on the multi−step statistical analysis including quantile g-computation (Q-gcomp), logistic regression model, orthogonal partial least squares discriminant analysis (OPLS-DA), random forest (RF) model and weighted quantile sum (WQS) regression, the top three essential trace elements among the 18 elements significantly associated with PCOS risk were cobalt (Co), stannum (Sn) and manganese (Mn), the top three heavy metals were lead (Pb), cadmium (Cd) and barium (Ba). The results of the BKMR model showed that mixtures of Pb, Cd and Ba were positively associated with the risk of PCOS, mixtures of Co, Sn and Mn were negatively associated with the risk of PCOS, mixtures of these six trace elements were negatively associated with the risk of PCOS at high concentrations, mixtures of 18 trace elements was negatively associated with the risk of PCOS. It states clearly that exposure to trace elements is associated with a decreased risk of PCOS, with trace essential elements possibly playing a greater role. In addition, we revealed that testosterone was significantly and positively mediating the association between Ba level and the risk of PCOS with mediated proportion of 0.07, testosterone was significantly and negatively mediating the association between Sn level and the risk of PCOS with mediated proportion of 0.14, LH/FSH ratio were significantly and negatively mediating the association between Co, Mn level and the risk of PCOS (with mediated proportion of 0.23 and 0.34, respectively). Our study indicates that eschewing heavy metals and supplementing properly with trace essential elements are conducive to reducing the risk of PCOS.